DNA damage repair promotion in colonic epithelial cells by andrographolide downregulated cGAS‒STING pathway activation and contributed to the relief of CPT-11-induced intestinal mucositis - Yuanyuan Wang; Bin Wei; Danping Wang; Jingjing Wu; Jianhua Gao; Haiqing Zhong; Yang Sun; Qiang Xu; Wen Liu; Yanhong Gu; Wenjie Guo (Elsevier, 2022)
Gastrointestinal mucositis is one of the most debilitating side effects of the chemotherapeutic agent irinotecan (CPT-11). Andrographolide, a natural bicyclic diterpenoid lactone, has been reported to possess anti-colitis activity. In this study, andrographolide treatment was found to significantly relieve CPT-11-induced colitis in tumor-bearing mice without decreasing the tumor suppression effect of CPT-11. CPT-11 causes DNA damage and the release of double-stranded DNA (dsDNA) from the intestine, leading to cyclic-GMP-AMP synthase (cGAS)‒stimulator of interferon genes (STING)-mediated colitis, which was significantly decreased by andrographolide both in vivo and in vitro. Mechanistic studies revealed that andrographolide could promote homologous recombination (HR) repair and downregulate dsDNA‒cGAS‒STING signaling and contribute to the improvement of CPT-11-induced gastrointestinal mucositis. These results suggest that andrographolide may be a novel agent to relieve gastrointestinal mucositis caused by CPT-11.